Giardia a model organism - Lujân, Hugo D.; Svärd, Staffan; SpringerLink (Online service). (Wien Springer, 2011)
Giardia is a relatively simple eukaryotic microbe, causing acute and chronic diarrhea which has been used as a model to understand complex biological processes occurring in eukaryotic cells. Further, due to its parasitic lifestyle, Giardia is an excellent system for the study of the mechanisms of adaptation and cell differentiation from the perspectives of molecular and cell biology. This book presents a comprehensive review of the current state of knowledge regarding all aspects of Giardia?s biology, including epidemiology, cell and molecular biology, genetics, pathogenesis, diagnostics, and clinical treatment. It was written by internationally renowned authors, the leading researchers in the field including several chapters with techniques and resources available for the study of this microorganism. Questions that need to be addressed to fully understand the molecular mechanisms of the parasite as well as the cause of its pathology are presented. Furthermore, Giardia's biology is compared with that of other parasites in relation to their complexity. This volume is an indispensable resource for researchers working with this parasite. It is a must for libraries and the bookshelves of everyone interested in the biology of parasites and early-branching eukaryotes.
Preface and Introduction -- Section I: Taxonomy and Epidemiology of Giardia -- 1 Taxonomy of Giardia Species -- 2 Epidemiology of Giardiasis in Humans -- 3 Waterborne and Environmentally-Borne Giardiasis -- 4 Giardia in Pets and Farm Animals, and Their Zoonotic Potential -- Section II: Molecular Biology of Giardia -- 5 Genomics of Giardia -- 6 The Glycoproteins of Giardia -- 7 Mass Spectrometric Analysis of Phospholipids and Fatty Acids in Giardia lamblia -- 8 Giardia Metabolism -- Section III: Cellular Biology of Giardia -- 9 The Ultrastructure of Giardia During Growth and Differentiation -- 10 Cell Cycle Regulation and Cell Division in Giardia -- 11 The Giardia Mitosomes -- 12 Signaling Pathways in Giardia lamblia -- 13 Transcription and Recombination in Giardia -- 14 Intracellular Protein Trafficking -- 15 Post-transcriptional Gene Silencing and Translation in Giardia -- 16 Antigenic Variation in Giardia -- Section IV: Pathology, Treatment and Diagnostics of Giardia and the Host Immune Response -- 17 Interaction of Giardia with Host Cells -- 18 Primary Microtubule Structures in Giardia -- 19 Pathophysiological Processes and Clinical Manifestations of Giardiasis -- 20 Immunology of Giardiasis -- 21 Vaccination Against Giardia -- 22 Diagnosis of Human Giardiasis -- Section V: Methods for Giardia Research -- 23 Methods for Giardia Culture, Cryopreservation, Encystation, and Excystation In Vitro -- 24 Synchronization of Giardia -- 25 Methods for Giardia Transfection and Gene Expression -- 26 Biological Resource Centers for Giardia Research.
Electronic reproduction.
Keywords: Giardia; Giardiasis; Electronic books